Integration of nonlinear models of flexible body deformation in multibody system dynamics - Schulze, Martin; Dietz, Stefan; Tuganov, Andrey; Lang, Holger; Linn, Joachim (The 2nd Joint International Conference on Multibody System Dynamics, 2012)
A simple transformation of the Equation of Motion (EoM) allows us to directly integrate nonlinear structural models into the recursive Multibody System (MBS) formalism of SIMPACK. This contribution describes how the integration is performed for a discrete Cosserat rod model which has been developed at the ITWM. As a practical example, the run-up of a simplified three-bladed wind turbine is studied where the dynamic deformations of the three blades are calculated by the Cosserat rod mode